Symptoms, functional status and quality of life in patients with controlled and uncontrolled atrial fibrillation: data from the RealiseAF cross-sectional international registry. Issue 3 (22nd September 2011) - Steg, P Gabriel; Alam, Samir; Chiang, Chern-En; Gamra, Habib; Goethals, Marnix; Inoue, Hiroshi; Krapf, Laura; Lewalter, Thorsten; Merioua, Ihsen; Murin, Jan; Naditch-Brûlé, Lisa; Ponikowski, Piotr; et al.
Abstract : Background: Rate control and rhythm control are accepted management strategies for atrial fibrillation (AF). Objective: RealiseAF aimed to describe the success of either strategy and the impact of control on symptomatic status of patients with AF. Methods: This international, observational, cross-sectional survey of patients with any history of AF in the previous year, recorded AF characteristics, management and frequency of control (defined as sinus rhythm or AF with resting heart rate ≤80 bpm). Results: Overall, 9665 patients were evaluable for AF control, with 59.0% controlled (sinus rhythm 26.5%, AF ≤80 bpm 32.5%) and 41.0% uncontrolled. Symptom prevalence in the previous week was lower in controlled than uncontrolled AF (55.7% vs 68.4%; p<0.001) and similar for patients in sinus rhythm versus AF ≤80 bpm (54.8% vs 56.4%; p=0.23). At the visit, AF-related functional impairment (EHRA class >I) was seen in 67.4% of patients with controlled AF and 82.1% of patients with uncontrolled AF (p<0.001). Quality-of-life (QoL, measured using EQ-5D) was better for patients with controlled versus uncontrolled AF using the Visual Analogue Scale (mean (SD) score 67.1 (18.4) vs 63.2 (18.9); p<0.001), single index utility score (median 0.78 vs 0.73; p<0.001), or five dimensions of well-being (all p<0.001). Irrespective of AF control, cardiovascular events had led to hospitalisation in the past year in 28.1%. Conclusion: AF control is not optimal. Control appears to be associated with fewer symptoms and better QoL, but even patients with controlled AF have frequent symptoms, functional impairment, altered QoL and cardiovascular events. New treatments are needed to improve control and minimise the functional and QoL burden of AF.